Maximum entropy and the existence of consistent aggregates: An application to U.S. banking - Amos Golan; Moshe Kim (Bank of Finland, 1992)
A non-parametric framework for testing the existence of aggregates is developed. The framework is based on the notion of the maximum entropy formalism which is applied to model the size distribution of firms. The theory, once presented, is applied to the US banking industry in order to test for the existence 'of a consistent output-aggregate. The existence of an output-aggregate in banking can facilitate much of the empirical research in this industry and shed some light on the industry's long-run market structure.
URN:NBN:fi:bof-201808021861
Keywords: 330